Optimisation for stealth target detection based on stratospheric balloon‐borne netted radar system. Issue 7 (1st August 2015) - Barbary, Mohamed; Zong, Peng
Abstract : This study deals with an improvement of radar cross section (RCS) of stealth target model such as F‐117A with a higher aspect vision, and proposes a new detection technique based on stratospheric balloon‐borne netted radar system. Normally, it is very difficult to statistically model a stealth target by conventional analytically probability density function (pdf) expressions. Thus, a novel non‐parametric detection technique using time difference of arrival (TDOA) and physical optics (PO) approximation method is proposed. Finally, Legendre orthogonal polynomials (LOP) using to reconstruct the pdf of stealth RCS predicted by PO. The potential problem of proposed scheme is instability of the platform caused by sudden gusts of winds. The balloon flight control is studied in detail by considering external force of wind that is typical random process with Dryden turbulence spectrum. The proposed geometrical structure of radar system is composed of one transmitter and multiple receivers. To achieve high accuracy of locating a stealth target, the proposed scheme uses accuracy RCS measurement to compute Stealth target position. Simulations demonstrate that proposed scheme using one transmitter and multiple balloon‐borne receivers give much higher location accuracy comparing to other geometrical systems because of increasing the PO – scattered field with higher aspect angles.